Aplicação da terapia fotodinâmica na redução de patógenos cariogênicos - Patricia Valente Araujo (2009)
The aim of this study was to evaluate the effect of photodynamic therapy (PDT) on caries lesions in vitro and in vivo, testing this procedure as an alternative to the usual treatment of caries. For in vitro procedures, associations between different light sources and photosensitizers agents were tested. The treatment which showed better performance in the lethal photosensitization of suspensions of Streptococcus mutans (ATCC 25175) was defined as a clinical protocol for the application of PDT in vivo. The study was approved by the Ethics Committee of the Federal University of Minas Gerais. Molars with deep active carious were selected from children of both genders aged between three years and nine years. Samples of carious dentin were removed before and after application of PDT and subjected to microbiological analyses by culture and real time PCR methods. As a clinical protocol of PDT, after five minutes of contact between the photosensitizer methylene blue (25mg/L) and the cavity, this cavity was irradiated for one minute by a red laser (Group I, n = 10) or an halogen light source (Group 2, n = 10). The results of the culture method showed that in the Group I, which associated the methylene blue to a red laser, the PDT showed no antimicrobial potential when used on caries lesions. For Group II (methylene blue + halogen light source), the statistical analysis showed differences between control and test groups and a reduction above 95% was observed, confirming the effectiveness of this therapy. When comparing the results of control groups with the results of the test groups by real time PCR, it was observed that PDT was not able to reduce the number of copies of DNA from S. mutans, when the halogen light was used. Further studies are needed before proposing a clinical application of PDT in the treatment of carious lesions.